Manfaat dan Peran Media Pembelajaran Bahasa Indonesia pada Era Digital - Seri Gustini; Erna Ikawati (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the benefits and roles of learning media in Indonesian language instruction in the digital era. The issue addressed in this research concerns the limited effectiveness of learning caused by the lack of integration of digital media in classroom practices. Using a descriptive qualitative approach through literature review and document-based analysis, this study identifies key findings related to the functions of learning media in enhancing motivation, strengthening linguistic understanding, supporting multimodal literacy, and improving learner autonomy. The results show that digital media provide more contextual, interactive, and adaptive learning experiences aligned with students’ needs. This research highlights the significance of media integration as an essential component of modern Indonesian language learning.